2020
DOI: 10.1136/jclinpath-2020-206871
|View full text |Cite
|
Sign up to set email alerts
|

Ran GTPase is an independent prognostic marker in malignant melanoma which promotes tumour cell migration and invasion

Abstract: AimsRan GTPase is involved in nucleocytoplasmic shuttling of proteins and is overexpressed in several cancers. The expression of Ran in malignant melanoma (MM) and its functional activity have not been described and were investigated in this study.MethodsThe prognostic value of Ran expression was tested in a series of 185 primary cutaneous MM cases using immunohistochemistry. The functional activity of Ran was investigated in the two melanoma cell lines. Ran expression was knocked down using two siRNAs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…RAN is a RAS-related GTPase with numerous cellular functions, including the transportation of molecules between the nucleus and cytoplasm, the regulation of cell cycle-related proteins, and the assembly of the mitotic spindle. Ran GTPase is overexpressed in several cancer types, and its high levels correlate with malignant features [ 49 , 50 , 51 ]. Another molecule at the crossroads of the KRAS pathway is the farnesyl pyrophosphate synthase (FPPS).…”
Section: Discussionmentioning
confidence: 99%
“…RAN is a RAS-related GTPase with numerous cellular functions, including the transportation of molecules between the nucleus and cytoplasm, the regulation of cell cycle-related proteins, and the assembly of the mitotic spindle. Ran GTPase is overexpressed in several cancer types, and its high levels correlate with malignant features [ 49 , 50 , 51 ]. Another molecule at the crossroads of the KRAS pathway is the farnesyl pyrophosphate synthase (FPPS).…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were also reported in colorectal cancer patients with PI3K and K-Ras mutations; increased Ran expression was associated with a shorter survival time [ 6 , 107 , 108 ]. Moreover, Ran is overexpressed in numerous human cancers, including those of the stomach [ 91 , 109 ], lung [ 6 , 8 ], head and neck [ 110 ], pancreas [ 111 ], ovary [ 112 ], malignant melanoma [ 5 ], colorectal [ 113 ], and kidney [ 96 ], but not in non-tumor tissue [ 5 ].…”
Section: The Overexpression Of Ran Alters Cellular Growth and Prolife...mentioning
confidence: 99%
“…The expression of Ran has also been shown to play a vital role in the regulation of mitosis and nucleocytoplasmic transport in tumor cells, further implicating it as a mediator of tumor cell survival [ 5 , 6 , 7 , 8 ]. Ran plays an important role in regulating the directionality of nucleocytoplasmic transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found RAN overexpression in the cells of several tumors, including neuroblastoma [ 26 ], breast cancer [ 27 , 28 ], pancreatic cancer [ 23 ], gastric cancer [ 29 ], and squamous cell carcinoma of the head and neck [ 30 ], indicating that it may influence cancer susceptibility. Knockdown of the RAN gene reduces expression of c‐Met and its downstream signaling target ERK1/2, significantly reducing the ability of A375 and G361 melanoma cells to migrate and invade [ 31 ]. RAN rs7132224 A>G was found to increase Wilms tumor risk [ 32 ].…”
Section: Introductionmentioning
confidence: 99%